(untitled) (Journal of Philosophy, Culture and Political Science, 2024)
As society undergoes transitions from one historical epoch to another, individuals’ perceptions of the expansive world surrounding them undergo transformations. The cosmos, regarded as the cradle of humanity, involves intricate and multifaceted connections with the universe. Evidence of ancient interactions is discernible through numerous archaeological findings and various remnants of ancient cultures. These interactions played a pivotal role in shaping the cognitive framework of individuals. The primary objective of this investigation is to ascertain the influence of ancient knowledge on the development of individuals’ philosophical self-awareness. Key patterns of a cosmocentric approach were identified, contributing significantly to the elevated appreciation of ancient knowledge in the lives of individuals. Contemporary perspectives on holism, globalism, and the noosphere underscore the imperative to elucidate the essence and significance of this knowledge in human life. Fundamental approaches and information regarding the evolution of ancient knowledge were scrutinized. It was deduced that in antiquity and the Middle Ages, a scientific paradigm of the world began to crystallize, impacting cosmocentric and theocentric models of the world and human existence. Conclusive remarks were drawn, indicating that the emergence of contemporary self-awareness precipitated the isolation of humans from nature, instigating a process of alienation. The loss of unity and connection with the cosmos resulted in humans distancing themselves from nature, culminating in the definitive establishment of a rationalistic worldview. Nevertheless, all developments and inquiries within philosophical disciplines contributed to the configuration of social life forms, irrespective of the rational or irrational criteria applied in thinking. The endeavors of ancient thinkers such as Aristotle or Plato to synthesize ideas about social development were distinguished by their universal, all-encompassing nature. Analogous scholarly endeavors persist in the present, albeit not at the same echelon. Ancient conceptualizations of societal life and the cosmos, alongside prognostication and pragmatic applications, are subject to investigation, enriching self-awareness, including its philosophical dimension. Consequently, studies of this nature contribute substantially to the continual expansion of our comprehension of the underpinnings of the contemporary human worldview. Keywords: worldview, philosophical foundations of worldview, ancient contacts and knowledge, history of civilization.